Formação de texturas cristalográficas em filmes finos de NbN - Schneider, Angélica Daiane (2017)
Niobium nitride (NbN) thin films can be hard and resistant not only to mechanical wear but also to chemically aggressive atmospheres. Additionally, they can present a superconducting transition in temperatures that are larger than classical BCS materials. But all these properties of the NbN thin film, and its performance in devices, strongly depends not only on its crystallographic structure, but also on the presence of crystallographic textures. In this work we approach the texture formation as a function of the thickness, in NbN thin films prepared by reactive magnetron sputtering onto Si substrates held at 300, 400, and 500°C. A transmition electron microscopy (TEM) image shows a columnar type morphology for the NbN deposited under our experimental conditions. The crystal structure and degree of texturization, for each thickness and temperature, were stablished by X-Ray diffractometry in the Bragg-Brentano configuration. Independent of the temperature of the substrate, two crystallographic textures of the cubic NbN ((200) and (111)) can be identified, but with contributions to the total volume that depends on the film thickness. Up to 300 nm, value that is almost independent of the substrate temperature, the grow of NbN with (111) planes parallel to the substrate dominates. Above this point, the picture inverts, and the material is mainly deposited along the h200i direction. This two-steps process is present even for the films deposite at 500°C, where the invertion in the process occurs together with the formation of NbN with hexagonal symmetry. Althought a similar behavior have been reported to TiN, this process was not up to now identified in NbN thin films. The results are discussed in terms of the models traditionally used for explain the formation of textures in nitrides.